# What is the answer to 1+2-4-3+4-3+3+2-44+39+2-6 ?

justaguide | College Teacher | (Level 2) Distinguished Educator

Posted on

The result of 1+2-4-3+4-3+3+2-44+39+2-6 has to be determined.

This is done quite simply by adding and subtracting the given numbers.

The result is -7

1+2-4-3+4-3+3+2-44+39+2-6 = -7

zumba96 | Student, Grade 11 | (Level 3) Valedictorian

Posted on

This is a problem that simply needs to have been added and subtracted as the problem goes along

1+2-4-3+4-3+3+2-44+39+2-6

-7

nisarg | Student, Grade 11 | (Level 1) Valedictorian

Posted on

1. 3 - 4 -3 + 4 - 3 + 3 + 2 - 44 + 39 + 2 - 6
2. -1 - 3 + 4 - 3 + 3 + 2 - 44 + 39 + 2 - 6
3. -4 + 4 - 3 + 3 + 2 - 44 + 39 + 2 - 6
4. -3 + 3 + 2 - 44 + 39 + 2 - 6
5. 2 - 44 + 39 + 2 - 6
6. -42 + 39 + 2 - 6
7. -3 + 2 - 6
8. -1 - 6
9. -7

jess1999 | Student, Grade 9 | (Level 1) Valedictorian

Posted on

1 + 2 - 4 - 3 + 4 - 3 + 3 + 2 - 44 + 39 + 2 - 6

To solve this equation you just simply have to add and subtract

3 - 4 -3 + 4 - 3 + 3 + 2 - 44 + 39 + 2 - 6

-1 - 3 + 4 - 3 + 3 + 2 - 44 + 39 + 2 - 6

-4 + 4 - 3 + 3 + 2 - 44 + 39 + 2 - 6

-3 + 3 + 2 - 44 + 39 + 2 - 6

2 - 44 + 39 + 2 - 6

-42 + 39 + 2 - 6

-3 + 2 - 6

-1 - 6

= -7

Wiggin42 | Student, Undergraduate | (Level 2) Valedictorian

Posted on

By the order of operations, we know that we do addition and subtraction in the order we read them from left to right. So:

1 + 2 - 4 - 3 + 4 - 3 + 3 + 2 - 44 + 39 + 2 - 6 =

3 - 4 - 3 + 4 - 3 + 3 + 2 - 44 + 39 + 2 - 6 =

-1 - 3 + 4 - 3 + 3 + 2 - 44 + 39 + 2 - 6 =

-4 + 4 - 3 + 3 + 2 - 44 + 39 + 2 - 6 =

0 - 3 + 3 + 2 - 44 + 39 + 2 - 6 =

-3 + 3 + 2 - 44 + 39 + 2 - 6 =

0 + 2 - 44 + 39 + 2 - 6 =

2 - 44 + 39 + 2 - 6 =

-42 + 39 + 2 - 6 =

-3 + 2 - 6 =

-1 - 6 =

-7